Effects of protected areas and climate change on the occupancy dynamics of common bird species in South Africa - Duckworth, Greg (Department of Statistical Sciences, 2019)
Protected areas are tracts of land set aside primarily for the conservation of biodiversity and natural habitats. They are intended to mitigate biodiversity loss caused by land-use change worldwide. Climate change has been shown to disrupt species' natural distributions and patterns, and poses a significant threat to global biodiversity. The goals of this thesis are to address these important issues, and understand how protected areas and climate change affect the range dynamics of common, resident bird species in South Africa. Common species were used because they have been shown to drive important ecosystem patterns, and a decline in abundance and diversity of common species can indicate drastic declines in ecosystem integrity. This thesis comprises four data chapters; in the first three I model the occupancy dynamics of 200 common, resident bird species in South Africa to gain an understanding of how the proportion of protected areas within a landscape affects common species. For the last data chapter, I examined the effects of protected areas and a changing climate on the range dynamics of Cape Rock-jumper (Chaetops frenatus), a species endemic to the southwestern part of South Africa and whose population is declining rapidly in response to climate change. I modelled its occupancy dynamics in relation to climate, vegetation, and protected area. Overall, my key findings show bird abundances vary widely as a function of protected areas, but on average, bird abundances are higher in regions with a higher proportion of protected areas, compared to regions with a lower proportion. I found that the conservation ability of protected areas was influenced by the type of land-use found in the surrounding landscape. For example, the extent of agricultural land in proximity to a protected area significantly increased the mean abundance of birds in that protected area, whilst the average abundance of most species was not affected by the extent of urban area near protected area. On average, species preferentially colonized and persisted within landscapes with a higher proportion of protected area, compared to landscapes with a lower proportion of protected area. However, protected areas were not able to slow the extinction rate for all species, and the average extinction rate for some groups of species actually increased as the extend of protected areas within a landscape increased. Furthermore, Cape Rock-jumper also preferentially occupied regions with higher proportions of protected area. Despite this, Cape Rock-jumper’s range is predicted to shrink considerably in response to a hotter and mildly drier climate forecast for the region. As a result, Cape Rock-jumper will likely be of conservation concern as the climate over its range continues to change. I conclude that, in general, protected areas are effective at conserving common bird species over a heterogeneous landscape in South Africa, and should be prioritised as key conservation strategies in the future. I further conclude that climate change will be a concern to an endemic species, and to biodiversity in general. This will likely place extra stress on the importance of protected areas to mitigate responses of species to climate change.